Final report on the update and maintenance of OpenFoodTox: EFSA's Chemical Hazards Database: S‐IN Soluzioni Informatiche. Issue 7 (4th July 2018) - Ceriani, Lidia; Ciacci, Andrea; Baldin, Rossella; Kovarich, Simona; Pavan, Manuela; Fioravanzo, Elena; Bassan, Arianna
Abstract : The present document is a summary of the update and maintenance of the EFSA's Chemical Hazards Database 'OpenFoodTox' that has been developed over the last 6 years to map hazards data as published in the EFSA opinions, statements and conclusions. More specifically, the repository holds summary data on identification of chemicals, document descriptors, hazard identification, and hazard characterisation. The repository includes data extracted from opinions and statements adopted by a number of EFSA panels including NDA (vitamins and minerals, novel foods, dietetic products), CONTAM (contaminants in the food chain, contaminants in the feed chain), FEEDAP (feed additives‐application linked to 1381/2003, feed additives‐application under to 1381/2003, feed additives‐other), AFC (food additives, food contact materials, nutrient sources, processing aids, flavourings), CEF (food contact materials, food manufacturing processes, processing aids, flavourings), ANS (food additives, nutrient sources) and the Pesticides unit. Substances which do not fall within the category of chemicals (e.g., microorganisms, fungi, nematodes, and enzymes) are excluded from EFSA's Chemical Hazards Database.